REAKSI PASAR INDONESIA ATAS PENGUMUMAN PEMINDAHAN IBU KOTA ISRAEL - Adfi, Agung Tri; Nurazi, Ridwan; Aisyah, Siti (JURNAL FAIRNESS, 2018)
The purpose of this study is to analyze the market reactions to the announcement of the capital of Israel movement to Jerusalem on the Indonesia Stock Exchange (IDX). The event study method is used to analyze market reactions and statistical significance to test the difference in abnormal return and trading volume activity between the observation period and the average between two sample groups. The sample was selected using a purposive sampling method which obtained two sample groups, namely companies with controlling shareholders from Europe which were recorded on November and December 2017 and companies that were included in the LQ-45 list in the period of August 2017 to January 2018.Statistical results show that the significant difference in abnormal return between the observation periods is only found in the period between before and during the event in each sample group, for the trading volume activity variable there is no difference between all observation periods in each sample group. The significance of the difference in the average between the two sample groups in the period when an event occurs is only found in the trading volume activity variable.